Catalyst-Free, Regioselective Ring Opening of Donor–Acceptor Cyclopropanes: Synthesis of Functionalized Mono- and Disulfides - Gopinath, Purushothaman; Chandrasekaran, Srinivasan (Synthesis, 2016)
Interesting sulfur compounds such as monosulfides, symmetrical disulfides, unsymmetrical disulfides, and other 1,3-bifunctionalized compounds were synthesized using benzyltriethylammonium tetrathiomolybdate, [BnNEt3]2MoS4, as the sulfur transfer reagent via regioselective ring opening of donor–acceptor cyclopropanes without the addition of any catalyst.
Keywords: cyclopropanes; ring opening; monosulfides; disulfides; thioesters